2017
DOI: 10.1007/s11606-017-4242-4
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care for Depression among Patients with Limited English Proficiency: a Systematic Review

Abstract: While limited by the number and variability of studies, the available research suggests that collaborative care for depression delivered by bilingual providers may be more effective than usual care among patients with LEP. Implementation studies of collaborative care, particularly among Asian and non-Spanish-speakers, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…The inclusion criteria were met by 128 studies; 115 were primary studies and 13 were systematic reviews [147][148][149][150][151][152][153][154][155][156][157][158][159]. Relevant data were extracted and tabulated to map the studies (additional file 2); separate tables summarised relevant systematic reviews (see Table 2 and additional file 3).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria were met by 128 studies; 115 were primary studies and 13 were systematic reviews [147][148][149][150][151][152][153][154][155][156][157][158][159]. Relevant data were extracted and tabulated to map the studies (additional file 2); separate tables summarised relevant systematic reviews (see Table 2 and additional file 3).…”
Section: Resultsmentioning
confidence: 99%
“…21,29 With regard to this secondary analysis specifically, CPIC was not powered to detect differences in racial/ethnic subgroups, and may therefore under-estimate the potential impact of community participatory interventions. Similarly, this study's limited sample size prevents nuanced examination of outcomes according to the diversity within the two racial/ ethnic groups themselves (eg, according to primary language or nation of birth among Latino participants 11 ). This study focuses on two large communities of color in the Los Angeles area, and as such it remains unclear how expanded collaborative care models based in CPPR processes would reduce disparities in mental health access and outcomes for other marginalized racial/ethnic groups and/or in other geographies throughout the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative care (CC) as a model for enhanced interdisciplinary care has been extensively studied within primary care (PC) settings and has demonstrated initial efficacy in depression treatment, including additional benefit to minority groups 8 and with particular benefit when culturally tailored and/or combined with language concordant interventions. [9][10][11] Of note however, PC-based terventions, 15 have brought to attention the potential limitations of PCbased treatment 9 and have prompted exploration of new models. 16 Community Partners in Care (CPIC) CPIC 2 was a group-level randomized trial designed to compare the efficacy of two expanded (multi-sector) collaborative care models of depression quality-improvement (QI) in under-resourced minority-majority communities.…”
mentioning
confidence: 99%
“…More recent studies have replicated this finding, with primary care patients enrolled in collaborative care programs reporting greater reductions in depressive symptoms and improvements in quality of life at 3 to 12 months follow-up compared to treatment as usual and co-location of behavioral health [ 42 44 ]. There has been an effort to disseminate collaborative care programs to more diverse populations, with encouraging results among racial/ethnic minorities [ 45 , 46 ] and patients with limited English language proficiency [ 47 ]. Observational studies from our certified PCMH at Mayo Clinic have indicated that patients participating in collaborative care remitted sooner and experienced residual depressive symptoms for a shorter length of time than patients receiving usual care [ 48 ].…”
Section: Components Of Depression Treatment In the Pcmhmentioning
confidence: 99%